Cityzenship: a study of transnational Chinese student returnees in three megacities in mainland China - Wang, Z (2021)
This thesis is a qualitative study of the return migration of overseas Chinese students. When overseas students return to China, many do not return to their hometown but usually land, work and settle down in one of China’s megacities: Beijing, Shanghai and Shenzhen. Their return migration is thus not only transnational migration but also internal-urban migration.